Teaching and Learning Process During the Covid-19 Pandemic - Maulinda Anjarsari; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research discusses the teaching and learning process that was implemented in the midst of the Covid-19 pandemic situation. Analyzing among others learning strategies, learning methods, media used and evaluation. In the process of this research using data retrieval techniques in the form of interviews, observations, photos during the research process is conducted. This research aims to find out how the teaching and learning process conducted by SD Muhammadiyah 1 Candi Sidoarjo in the midst of the Covid-19 pandemic. The results show that there are several slightly different strategies and media in the teaching and learning process that take place. One of them is the implementation. Before the pandemic the teaching and learning process was carried out normally face-to-face. However, during a pandemic like this the learning process is done online. But the learning process or learning activities such as the pray when going to start the learning process is still carried out such as reading prayers, singing songs and so on. Everything is the same as when normal learning is just the implementation online or virtual.